Economic and Social Impact of Islamic Inheritance Distribution : (an Analysis of The Development and Adaptation of Inheritance Law in the Modern Context) - Mohammad Adnan; Badrah Uyuni; Mahfuz Mahfuz; Sarbini Anim (Institut Agama Islam Miftahul Ulum Pamekasan, 2024)
This study examines the economic and social impacts of the distribution of Islamic inheritance and the adaptation of inheritance law in a modern context. Islamic inheritance law stipulated in the Quran and Hadith provides clear guidelines on the division of inheritance, but its implementation often faces various challenges, including delays in the distribution and uncertainty of rights. This study uses qualitative methods with observation and literature review to explore how Islamic inheritance law affects wealth distribution, economic and social justice, and adaptation to social and cultural changes. The study found that inheritance sharing plays an important role in creating economic and social justice, but is often hampered by a lack of understanding, delays, and internal family disputes. The implementation of technology and increased inheritance law education are expected to reduce disputes and increase compliance. This study also recommends the role of scholars and scholars in providing guidance and the need for a firmer legal system to overcome existing challenges. Further research is suggested to explore the impact of technology in inheritance management, case studies of law implementation in various communities, and evaluation of the role of ulama and the impact of inheritance law education on legal compliance.